It’s All About the People:: Cultural Intelligence (CQ) as a Force Multiplier in the Contemporary Operating Environment - Spencer, Emily (Journal of Conflict Studies, 2009)
ABSTRACT Militaries spend enormous amounts of money, time, and energy ensuring that their troops are trained on weapon systems, vehicles, and equipment. They spend small fortunes on preparatory exercises and training to test tactics, techniques, and procedures (TTPs); drills; and general soldier proficiency and effectiveness should they need to exercise force protection, demonstrate a deterrent posture, or actually fight during an operation. This preparation and expenditure is only prudent. However, what makes less sense is that, comparatively speaking, very little effort, if any at all, is spent solving the "people puzzle." In reality, most stability and counter-insurgency operations are all about the people. The importance of people is true at all levels, whether dealing with the adversaries, host nation population, international community, and even one"s own nation. To be successful in these potentially diverse environments, cultural intelligence (cultural quotient or CQ), that is the ability to recognize the shared beliefs, values, attitudes, and behaviors of a group of people and, most importantly, to apply this knowledge toward a specific goal, is critical. The fact is, understanding the people you work with makes for smoother relationships, better communication and comprehension, and, therefore, more effective results. Grasping differences in how others think, behave, make decisions, view the world, and interpret actions assists in providing strategies and options in how best to engage them to achieve your own objectives. Furthermore, a better understanding of one"s adversaries is equally as empowering. Abandoning preconceived, superficial, or erroneous perceptions and actually endeavoring to fully comprehend the "enemy" can provide invaluable insights into their attitudes, behaviors, decision-making processes, and motivations. In all, CQ is an underused tool that provides enormous capability to empower military personnel and assist them in achieving mission success. It is a force multiplier that is relatively inexpensive and, if properly harnessed, can furnish a return on investment far in excess of its cost. After all, conflict in general, and military operations specifically, are all about the people.